Implementasi SDGs-12 melalui inovasi bio-leather limbah ampas sagu untuk potensi produk kerajinan lukis aplikatif - Suseno, Bayu Aji; Utami, Putri Prabu; Satwikasanti, Winta Tridhatu; Ponimin, Ponimin; Rony, Rony; Hidayat, Anwar (Institut Seni Indonesia Yogyakarta, 2025)
The number of sago processing industries in Jayapura Regency has the potential to increase sago pulp fiber waste that is still not being optimally utilized. This study aims to address the problem of sago pulp waste by turning it into functional and aesthetic handicraft products using painting techniques. The design was carried out through exploration using the research through design (RTD) method, which consists of the stages of understanding material characteristics, exploring materials, and implementing materials. Data collection techniques used observation and interviews to gain an in-depth understanding of the sago waste processing from sago starch (flour) processing from sago trunk (tokok) grating, extraction, sedimentation, and drying. Samples of sago pulp waste were taken from the sago forest located in Kampung Harapan, Sentani District, East Jayapura Regency. The sample characteristics in the research population were two-week-old sago pulp fiber waste that had been crushed from the sago processing of sago pith or trunk contents. The result of this research is a composite sheet in the form of bio-leather from sago pulp waste that is used as a material for making fashion products. This research focuses on the application of a green economy by developing craft raw materials to support Sustainable Development Goals (SDGs) number 12, namely responsible consumption and production.